Rezension von: Hausmaninger, Herbert; Selb, Walter, Römisches Privatrecht - Maisch, Andreas (Württembergisch Franken, 1999)
Herbert Hausmaninger u. Walter Selb, Römisches Privatrecht, Wien, Köln, Weimar (Böhlau) 8/1997. 528 S.